Implementation Of Marketing Strategies In Increasing Product Sales - Siregar, Saparuddin; Putra, Irhamsyah; Dila Sari, Cut (Universitas Islam Negeri Sumatera Utara, 2023)
This journal discusses the implementation of marketing strategies as the main key in increase product sales in the Ara fashion industry. This research uses a case study approach to analyze how effective marketing strategies can contribute to sales growth of a product. The methodology involves surveys, interviews, and data analysis to measure the impact of implemented marketing strategies. The research results show that the use of appropriate marketing strategies, such as utilizing social media, improving branding, and product promotion, can significantly increase consumer awareness and, in turn, accelerate the rate of sales. The practical implications of these findings can provide valuable guidance for industry players in designing effective marketing strategies to improve the sales performance of their products.